Usefulness of PCR-HRMA in identification of non-fermentative Gram-negative rods recovered from patients suffering from cystic fibrosis or chronic obstructive pulmonary disease - Navrátilová, Lucie; Safářová, Dana; Raclavský, Vladislav (Folia microbiologica, 2014)
Adequate treatment of microbial infections requires rapid and accurate identification of the etiological agent. In routine diagnostics, identification of bacteria conventionally relies on phenotypic testing, which can be hindered by phenotypic variations. Therefore, genotyping techniques should perform faster and more accurately. Recently, the technique of high-resolution melting analysis (HRMA) of PCR amplicons promises to provide a convenient and economic tool of genotypic identification. In our study, we performed prospective routine testing of a PCR-HRMA system that was recently published in a proof-of-the-principle study. The system was evaluated by analysing 275 clinical isolates of bacteria acquired from 65 patients suffering from cystic fibrosis or chronic obstructive pulmonary disease. Our results show that its routine use may result in partial worsening of its discriminatory power; however, it still outmatched conventional phenotyping in the group of non-fermentative Gram-negative rods. Moreover, when supplemented by rapid, simple and economic oxidase test, it can be even simplified for more economic performance.
Keywords: Gram-Negative Bacterial Infections; Transition Temperature; DNA bakterií; Molecular Diagnostic Techniques; Humans; Respiratory Tract Infections; diagnostické techniky molekulární; Bacteriological Techniques; lidé; Cystic Fibrosis; DNA, Bacterial; tranzitní teplota; Gram-Negative Aerobic Rods and Cocci; polymerázová řetězová reakce; gramnegativní aerobní tyčinky a koky; infekce dýchací soustavy; chronická obstrukční plicní nemoc; cystická fibróza; Polymerase Chain Reaction; Pulmonary Disease, Chronic Obstructive; gramnegativní bakteriální infekce; prospektivní studie; bakteriologické techniky; Prospective Studies